The pelagic squid assemblage of the Kerguelen Axis - Lin, D; Rowan Trebilco; Andrea Walters; Zhu, G; Chen, X (2019)
Squids are increasingly acknowledged as an ecologically important group in Southern Ocean ecosystems, and most are represented exclusively by endemic species due to the biological barrier of Antarctic Polar Front. However, there are still large gaps in their now-known biogeographic components, especially the population diversity in the Indian sector. We thus present a first evaluation of diversity and distribution of the squid populations in the Kerguelen Plateau, based on an ecosystem study of the Kerguelen Axis conducted between January and February 2016. A total of 801 squid specimens were collected from 36 stations, at depths from the surface to 1 000 m and were identified to seven species from six families, including Alluroteuthis antarcticus, Bathyteuthis abyssicola, Galiteuthis glacialis, Mastigoteuthis psychrophila, Mesonychoteuthis hamiltoni, Psychroteuthis glacialis and Slosarczykovia circumantarctica . Species composition was dominated by G. glacialis and P. glacialis , which accounted for 68.79% and 11.24% of the total collection respectively. We examined geographic niche breadth of these species in terms of their distributions across stations and with depth. All of these species exhibited a broad niche breadth, being the Shannon-Wiener’s niche breadth index (B i ) from 1.91 to 8.43. Variations of diversity index were estimated in a range of 0.39 to 1.56, and most of the peak diversity stations were found at the short deep-sea slope area and deep-sea basin. This variation was consistent with the bathymetric gradient of depth, although the relationship was not statistically significant. In addition, the highest diversity was detected in the top 200 m of the water column, with an occurrence >50% for most species at this depth stratum. This study demonstrates the squids’ population diversity in the southern Kerguelen Plateau, with new insights into their endemicity and diversity in this biologically important area.